2008
DOI: 10.1200/jco.2008.16.6231
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Characteristics of Patients With BRCA-Positive and BRCA-Negative Breast Cancer

Abstract: These results suggest that tumors associated with BRCA1 mutations may be divided into two distinct groups, triple-negative and non-triple-negative groups. Future studies should seek to determine whether patients with BRCA1 mutations and triple-negative breast cancer respond to treatment better than BRCA-negative patients with similar tumor pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
367
4
19

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(444 citation statements)
references
References 25 publications
35
367
4
19
Order By: Relevance
“…These mice develop mammary tumors with full penetrancy and a median tumor latency of 6.3 months (Shafee et al 2008). In line with recent reports (Atchley et al 2008;Tung et al 2010), both ERa-positive and ERa-negative tumors were identified and p63 expression was up-regulated. These findings raise the possibility that the cells of origin in BRCA1-mediated breast carcinogenesis may be heterogeneous.…”
Section: Transgenic Mouse Models Of Brca-associated Breast Cancersupporting
confidence: 74%
See 1 more Smart Citation
“…These mice develop mammary tumors with full penetrancy and a median tumor latency of 6.3 months (Shafee et al 2008). In line with recent reports (Atchley et al 2008;Tung et al 2010), both ERa-positive and ERa-negative tumors were identified and p63 expression was up-regulated. These findings raise the possibility that the cells of origin in BRCA1-mediated breast carcinogenesis may be heterogeneous.…”
Section: Transgenic Mouse Models Of Brca-associated Breast Cancersupporting
confidence: 74%
“…Earlier studies indicated that the majority of BRCA1-associated cancers are triple (ERa, PR, and HER-2) negative, basal-type breast cancers (reviewed in Lynch et al 2008). However, recent reports show that BRCA1-associated breast cancers can be ERa-and PR-positive, especially in aged patients (Atchley et al 2008;Tung et al 2010). The BRCA1 gene encodes a protein of 1863 amino acids with a predicted molecular weight of 220 kDa (Miki et al 1994).…”
Section: The Brca Pathwaysmentioning
confidence: 99%
“…tumours that do not express estrogen and progesterone receptor genes or the tyrosine kinase HER-2/neu) than BRCA2-related and sporadic breast cancers (87). Triplenegative tumours are more often poorly differentiated and associated with poorer survival (88).…”
Section: Brca-related Breast Cancermentioning
confidence: 99%
“…6 Overall, breast tumors resulting from BRCA1 mutations are most frequently TN (57%), 7 or ER + breast cancers (34%), 8 and are rarely HER2 + breast cancers (about 3%). 9 While TN tumors are often characterized by low expression of BRCA1, 10 because BRCA1 mutations are quite rare, they only account for approximately 10-20% of the TN tumors.…”
mentioning
confidence: 99%